2012
DOI: 10.1007/s00264-011-1459-4
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroscopy: evolution, current practice and future developments

Abstract: Arthroscopic examination and treatment is an ever-increasing part of modern orthopaedic practice in this age of minimally invasive surgery. Arthroscopic procedures have been widespread in surgery of the knee and the shoulder for many years; however, the hip until relatively recently, has been largely neglected. Even now hip arthroscopy is not widely available; this may be due to the complexity of the procedure, the requirement of specialist equipment and a reportedly long learning curve. On the other hand, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 53 publications
0
45
0
1
Order By: Relevance
“…For their management, open or arthroscopic labrum repair, impinging bone excision or microfracture have been advocated [6]. There is a trend towards less invasive procedures, with high rates of success when these pathologies are treated arthroscopically [9][10][11]. The best timing for arthroscopic knee surgery reported for anterior cruciate ligament lesions is within the first year of injury [12], but there is no study describing the best timing for hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…For their management, open or arthroscopic labrum repair, impinging bone excision or microfracture have been advocated [6]. There is a trend towards less invasive procedures, with high rates of success when these pathologies are treated arthroscopically [9][10][11]. The best timing for arthroscopic knee surgery reported for anterior cruciate ligament lesions is within the first year of injury [12], but there is no study describing the best timing for hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopy is our preferred approach to an amenable deformity, as it may spare extensive soft tissue dissection, expedite recovery, and be associated with fewer complications [76][77][78]. Contraindications to hip arthroscopy in the treatment of FAI include anatomic or pathologic limitations to adequate joint distraction (severe acetabular protrusion, heterotopic ossification), femoral head osteonecrosis, posterior femoral cam-type deformity, extra-articular trochantericpelvic impingement, and advanced degenerative joint disease [79,80]. Relative contraindications may include significant posterosuperior cam-type deformity, profunda deformity, or other anatomic variants that may be technically challenging to safely access and thoroughly address arthroscopically and vary significantly based on surgeon experience and ability.…”
Section: Indications For Arthroscopic Approachmentioning
confidence: 99%
“…Recent numerous research studies have reported that satisfactory clinical results in the treatments of hip labral lesions and other diseases could be achieved with the use of hip arthroscopy [5][6][7][8][9]. However, it remains unclear if labral lesions concomitant with acetabular dysplasia could achieve great clinical efficacy when treated with hip arthroscopic labral debridement.…”
Section: Introductionmentioning
confidence: 96%